A General and Efficient Method to Access Tetracyclic Spirooxindole Derivatives. Issue 3 (5th December 2014) - El Bouakher, Abderrahman; Massip, Stéphane; Jarry, Christian; Troin, Yves; Abrunhosa‐Thomas, Isabelle; Guillaumet, Gérald
Abstract: An efficient, simple, and convenient synthetic procedure for the synthesis of tetracyclic spirooxindole derivatives, starting from N ‐protected isatins and 2‐fluoropyridine, was successfully developed. It enables the facile formation of a new class of spirooxindoles in which the oxindole core is fused with various heterocycles at the C‐3 position. Abstract : Tetracyclic spirooxindoles were easily prepared from N ‐protected isatins and 2‐fluoropyridine, leading to fused C‐3 oxindole heterocycles in good yields.